Windows of the Museum of Fine Arts, ca. 1876-1909 - Unknown (Tufts Archival Research Center, 2005)
View of a set of windows on the Museum of Fine Arts building, located on St. James Avenue at Copley Square between Dartmouth Street to the southwest and Trinity Place to the northeast. Copyprint 9 1/8 x 7 3/16 Photographs